Pelatihan Pembuatan Hand Sanitizer kepada Masyarakat Desa Tangguh di Kp. Pasir Honje, Ds. Sukawening Kec. Ciwidey Kab. Bandung - Isma Dwi Kurniawan; Yani Suryani; Anggita Rahmi Hafsari; M. Agus Salim; Tri Cahyanto; Ayuni Adawiyah; Musa'adah Musa'adah; Siska Tridesianti (Universitas Muhammadiyah Semarang, 2021)
The Covid-19 pandemic that has been attacked almost all countries in the world since 2020 has changed the lifestyle and habits of peoples globally. Since this outbreak until now, peoples in all countries including in Indonesia must implement the health protocols to reduce the rate of virus transmission. One of them is by maintaining hand hygiene by washing hands using soap or hand sanitizer (HS). HS is used as an alternative in conditions which is difficult to washing hand. But, rural communities, especially in Tangguh Village in Kampung Pasir Honje, Sukawening, Ciwidey, Bandung Regency, are currently unable to use it due to limited access and economy. Training of making HS for the community can be a solution in overcoming this problem. Thie aims of this activity to provide skills to the people of Tangguh Village to make hand sanitizers made from alcohol and non alcohol. Method: conducted by lectures and do questions and answers about HS and then direct practice of making HS. Result: All participants can make hand sanitizers well. There are 2 types of HS that have been successfully made by the community, namely HS containing alcohol and HS free of alcohol. The alcohol content in the first type is around 60-70%, while the alcohol-free HS is made from betel leaf extract because it contains antibacterial compounds. The results of the evaluation show that 50% of the participants stated that they were very satisfied with the implementation of this activity and about 92% stated that this activity was very beneficial for them.